Rasch analysis of the Back Pain Attitudes Questionnaire (Back-PAQ). Issue 13 (19th June 2022) - Krägeloh, Chris; Medvedev, Oleg N.; Dean, Sarah; Stanley, James; Dowell, Anthony; Darlow, Ben
Abstract: Context: As psychosocial factors have been recognised as significant predictors of the recovery trajectory from chronic back pain, the 34-item Back Pain Attitudes Questionnaire (Back-PAQ) was developed based on themes obtained from patient interviews, but previous psychometric analyses with a general population sample revealed uncertainty around the factor structure of the instrument. Objectives: To provide more detailed information about the psychometric properties of the Back-PAQ when used with participants from the general population and also to test the internal validity of the tool for use with General Practitioners (GPs). Methods: After applying partial-credit Rasch analysis with a sample of participants from the general population ( n  = 600), a replication analysis was conducted with a sample of GPs ( n  = 184). This approach permitted examination of sample-specific personal factors for differential item functioning. Subtests were used to differentiate between local dependency due to underlying dimensionality from local dependency due to method effects. Results: A unidimensional fit to the Rasch model was achieved after 14 misfitting items had been deleted. The final 20-item solution also fit with a sample of 184 GPs. In both cases, the Back-PAQ-20 demonstrated good reliability (PSI ≥ 0.80), with no evidence of differential item functioning by personal factors. Conclusion: The ordinal-to-interval conversion algorithms presented here further enhance the precision of the scale and permit analysis of Back-PAQ-20 scores using parametric statistics. The present study provided evidence for valid and reliable assessment of the back pain recovery beliefs of both users as well as providers of health services. IMPLICATIONS FOR REHABILITATION: Psychosocial factors have been recognised as significant predictors of the recovery trajectory from chronic back pain. The 34-item Back Pain Attitudes Questionnaire (Back-PAQ) was developed based on themes obtained from patient interviews, but previous psychometric analyses with a general population sample revealed uncertainty around the factor structure of the instrument. The 20-item version of the Back Pain Attitudes Questionnaire (Back-PAQ) is shown here to have strong psychometric properties for administration with users and providers of health services.